Enhanced High-Temperature Cycling Stability of Garnet-Based All Solid-State Lithium Battery Using a Multi-Functional Catholyte Buffer Layer - Zhao, Leqi; Zhong, Yijun; Cao, Chencheng; Tang, Tony; Shao, Zongping (2024)
Thermally stable catholyte buffer layer was fabricated via incorporating a multi-functional flame-retardant triphenyl phosphate additive into poly(ethylene oxide). The optimized catholyte buffer layer enabled thermal and electrochemical stability at interface level, delivering comparable cycling stability of garnet-based all solid-state lithium battery, i.e., capacity retention of 98.5% after 100 cycles at 60 °C, and 89.6% after 50 cycles at 80 °C. Exceptional safety performances were demonstrated, i.e., safely cycling behavior at temperature up to 100 °C and spontaneous fire-extinguishing ability.